2020
DOI: 10.1259/bjr.20190974
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of <3 cm renal tumors by ultrasonography: a rapid, quantitative, elastography self-corrected contrast-enhanced ultrasound imaging mode beyond screening

Abstract: Objectives: To assess the combined diagnostic strategy of contrast-enhanced ultrasound (CEUS) and acoustic radiation force impulse (ARFI) in the precise differential diagnosis of clear cell renal cell carcinoma (CCRCC) and urothelium carcinoma of the renal pelvis (UCRP) with other small renal tumors (SRTs) <3 cm in size. Methods: The elastography self-corrected CEUS (ESC) mode was established to perform the quantitative differential diagnosis of SRTs (<3 cm). The kidney shear wave velocity (SWV) value recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
0
15
2
1
Order By: Relevance
“…These tumor features were reported to be associated with poor prognosis. In addition, we found that PC absence was related to small size, female, and low nuclear grade tumors, which appeared to result in good prognosis 25–27 . This is inconsistent with previous findings probably due to differences in tumor stage of patients in our study in relation to patients in other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These tumor features were reported to be associated with poor prognosis. In addition, we found that PC absence was related to small size, female, and low nuclear grade tumors, which appeared to result in good prognosis 25–27 . This is inconsistent with previous findings probably due to differences in tumor stage of patients in our study in relation to patients in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we found that PC absence was related to small size, female, and low nuclear grade tumors, which appeared to result in good prognosis. 25 , 26 , 27 This is inconsistent with previous findings probably due to differences in tumor stage of patients in our study in relation to patients in other studies. Moreover, we only included patients with small RCCs instead of all renal tumors as reported in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“… 6 The incidence of RCC has increased by 3.7% per year. 7 , 8 Due to the improvement of imaging technology, the incidence of localized early T1 tumors increased the most. 9 It is now widely accepted that most stage T1 RCCs have a favorable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…These masses have TNM staging of T1a and can be further subdivided into two stages: T1a1 (≤2 cm) and T1a2 (2–4 cm), based on significantly different survival rates associated with different treatment (e.g., observation, radiofrequency thermal ablation, partial or total nephrectomy) for the two sizes 6 . The incidence of RCC has increased by 3.7% per year 7,8 . Due to the improvement of imaging technology, the incidence of localized early T1 tumors increased the most 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic radiation force impulse imaging (ARFI) as a new technology is able to differentiate between malignant and benign renal masses by providing shear wave velocity values to quantify the elasticity of renal masses. [ 10 12 ] However, there are still various findings, and no systematic review has specifically assessed this issue. [ 13 19 ] Therefore, we will carry out a systematic review and meta-analysis to synthesize the diagnostic value of ARFI for renal masses.…”
Section: Introductionmentioning
confidence: 99%